The Review of Foreign Language Learning Motivation - Yang, Yunyi (Transactions on Social Science, Education and Humanities Research, 2024)
This review aims to discuss some research about different kinds of learning motivations in foreign language learning. By reviewing some of the passages about foreign language learning motivations before, it could be easy to find out that motivation is one of the most principal factors in foreign language learning which may make a great difference in the learning strategies and achievements. so that this review makes a discussion about the way different kinds of foreign language learners are affected by different kinds of learning motivations and what is the most common motivations in different kinds of learners. At the same time, there are a lot of passages that show that there is a relationship between motivation and the demotivation which should not be ignored. So, this review also organized some previous passages and made some discussion on the four different kinds of factors that could demotivate people in their foreign language learners.